Predictive and Prognostic Brain Metastases Assessment in Luminal Breast Cancer Patients: FN14 and GRP94 from Diagnosis to Prophylaxis - Martínez-Aranda, Antonio; Hernández, Vanessa; Moreno, Ferran; Baixeras, Núria; Cuadras, Daniel; Urruticoechea, Ander; Gil-Gil, Miguel; Vidal, Noemí; Andreu, Xavier; Seguí, Miquel A.; Ballester, Rosa; Castella, Eva; et al. (Frontiers in Oncology, 2017)
FN14 has been implicated in many intracellular signaling pathways and GRP94 is a well-known endoplasmic reticulum protein regulated by glucose. Recently, both have been associated with metastasis progression in breast cancer patients. We studied the usefulness of FN14 and GRP94 expression to stratify breast cancer patients according their risk of brain metastasis (BrM) progression. We analyzed FN14 and GRP94 by immunohistochemistry in a retrospective multicenter study using tissue microarrays from 208 patients with breast carcinomas, of whom 52 had developed brain metastasis. Clinical and pathological characteristics and biomarkers expression in Luminal and non-Luminal patients were analyzed using a multivariate logistic regression model adjusted for covariates, and brain metastasis-free survival was estimated using the Kaplan-Meier method and the Cox proportional hazards model. FN14 expression was associated with brain metastasis progression mainly in Luminal breast cancer patients with a sensitivity (53.85%) and specificity (89.60%) similar to Her2 expression (46.15% and 89.84%, respectively). Moreover, the likelihood to develop BrM in FN14 positive Luminal carcinomas increased 36.70 fold (3.65-368.25, p= 0.002). Furthermore, the worst prognostic factor for brain metastasis-free survival in patients with Luminal carcinomas was FN14 overexpression (HR=8.25; 95% CI: 2.77-24.61; p=0.00015). In these patients GRP94 overexpression also increased the risk of BrM (HR=3.58; 95%CI: 0.98-13.11; p=0.054 -Wald test). Therefore, FN14 expression in Luminal breast carcinomas is a predictive/prognostic biomarker of brain metastasis, which combined with GRP94 predicts brain metastasis progression in non-Luminal tumors 4.04 fold (1.19-8.22, p=0.025), suggesting that both biomarkers are useful to stratify brain metastasis risk at early diagnosis. We propose a new follow-up protocol for the early prevention of clinical brain metastasis of breast cancer patients with brain metastasis risk.